2016
DOI: 10.1093/mnras/stw1678
|View full text |Cite
|
Sign up to set email alerts
|

The magnetic field and dust filaments in the Polaris Flare

Abstract: In diffuse molecular clouds, possible precursors of star-forming clouds, the effect of the magnetic field is unclear. In this work we compare the orientations of filamentary structures in the Polaris Flare, as seen through dust emission by Herschel, to the planeof-the-sky magnetic field orientation (B pos ) as revealed by stellar optical polarimetry with RoboPol. Dust structures in this translucent cloud show a strong preference for alignment with B pos . 70% of field orientations are consistent with those of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 69 publications
10
57
1
Order By: Relevance
“…Figure 5 shows that the B-field lies roughly parallel to this subfilament, again as seen in Taurus (Palmeirim et al 2013). Similar behavior is also seen in the low-density striations in the Polaris Flare region (Ward- Thompson et al 2010;Panopoulou et al 2016).…”
Section: Discussionsupporting
confidence: 68%
“…Figure 5 shows that the B-field lies roughly parallel to this subfilament, again as seen in Taurus (Palmeirim et al 2013). Similar behavior is also seen in the low-density striations in the Polaris Flare region (Ward- Thompson et al 2010;Panopoulou et al 2016).…”
Section: Discussionsupporting
confidence: 68%
“…Likewise, using the same method and the results presented in Chapman et al (2011) it is found that in the northwest part of the Taurus molecular cloud the ratio of the turbulent to the ordered component of the magnetic field is ∼ 11%. In general, the ratio of the ordered to turbulent component in molecular clouds can be up to ∼ 75% (Houde et al 2016) and, within uncertainties, it can also be up to 40% in regions where striations appear (Panopoulou et al 2016b). For the strength of the magnetic field in the striations region in the Polaris flare, Panopoulou et al (2016b) reported values that ranged up to ∼ 80 µG.…”
Section: Mhd Wavesmentioning
confidence: 96%
“…In general, the ratio of the ordered to turbulent component in molecular clouds can be up to ∼ 75% (Houde et al 2016) and, within uncertainties, it can also be up to 40% in regions where striations appear (Panopoulou et al 2016b). For the strength of the magnetic field in the striations region in the Polaris flare, Panopoulou et al (2016b) reported values that ranged up to ∼ 80 µG. Since striations appear in regions of well ordered magnetic field our reference value for the amplitude of the perturbation is 15% the background value of each perturbed quantity.…”
Section: Mhd Wavesmentioning
confidence: 98%
See 1 more Smart Citation
“…XXXV, 2016, see Figs. 1b & 1c), a trend also seen in optical and near-IR polarization observations (Chapman et al, 2011;Palmeirim et al, 2013;Panopoulou et al, 2016;Soler et al, 2016). There is also a hint from Planck polarization observations of the nearest clouds that the direction of the magnetic field may change within dense filaments from nearly perpendicular in the ambient cloud to more parallel in the filament interior (cf.…”
Section: Insights From Herschel and Planck: A Filamentary Paradigm Fomentioning
confidence: 64%